In vivo evaluation of Catharanthus roseus L. (pink) extracts against Rigidoporus microporus on rubber (Hevea brasiliensis) seedlings - Zahari, Rozihawati; Terhem, Razak; Halimoon, Normala; Ahmad, Mohd Farid; Abdullah, Nor Hayati (Asian Society of Pharmacognosy, 2019)
Hevea brasiliensis (rubber) is an important species in rubber industries. The species is often attacked by Rigidoporus microporus in the plantations and chemical fungicides have been widely used to control this fungus. However, fungicides contribute to human health problems and environmental pollutions. To address the issues, bio-fungicide from the plant sources is an innovative alternative to replace the chemical fungicide. Thus, the objectives of the study were to investigate the effect of Catharanthus roseus extract in different concentrations against R. microporus on rubber seedlings. The efficacy of C. roseus extracts against R. microporus was assessed based on healthy effects percentage of the rubber seedlings, by assessing the symptoms on leaves and roots. The assessment was based on disease index (DI) and disease suppression (DS%). The DI results showed, at 2000 μg/mL was the most effective against R. microporus on rubber seedlings with level disease index of level 0 (0%) compared to 1500 and 1000 μg/mL with level 2 (26 - 50%), and level 4 (76 - 100%), respectively. The DS% results also showed that the extract was most effective at 2000 μg/mL in controlling the growth of R. microporus on rubber seedlings with a value of 100% compared to 1500 and 1000 μg/mL with a value of 0.0%. Hence, C. roseus extract might be suitable use as a biofungicide for controlling R. microporus on rubber crops.